A method for preparing a copper-plated polymer film and a device for using the same

By forming a polymer-copper mixed layer on the surface of the polymer film and depositing a multi-layer copper and tin layer, the problem of low bond strength of the copper plating layer in the prior art is solved, and high temperature stability and long-term bond strength are maintained.

CN116288162BActive Publication Date: 2025-03-04ZHUHAI KAISAIAO SURFACE TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310289321.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-23
Publication Date
2025-03-04
Estimated Expiration
2043-03-23

AI Technical Summary

Technical Problem

In the existing COF technology that uses magnetron sputtering to plating copper on the polymer surface, the bonding strength of the copper plating layer is relatively low, especially in high temperature environments, the copper plating layer is prone to fall off, and the thinner the copper plating layer, the weaker the bonding strength.

Method used

A polymer-copper hybrid layer is formed by implanting a high-energy copper ion beam on the surface of the polymer film, and then a low-energy copper ion beam is deposited on the surface to form a first copper layer, and then a second copper layer is deposited using electron beam evaporation, and a low-energy tin ion beam is deposited on the surface to form a tin antioxidant layer.

Benefits of technology

The bonding strength between the copper layer and the polymer film is significantly improved, the stability of the copper plating layer is ensured in a high temperature environment, and the oxidation of the copper layer is reduced through the tin antioxidant layer, and the retention time of the bonding strength is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116288162B_ABST
    Figure CN116288162B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of thin film surface metallization, and in particular to a method for preparing a copper-plated polymer film and a device for use. The method for preparing a copper-plated polymer film provided by the present invention comprises injecting a high-energy copper ion beam into the surface of a polymer film, forming a polymer-copper mixed layer on the surface of the polymer film, and the beam current intensity of the high-energy copper ion beam is ≥10mA; depositing a low-energy copper ion beam on the surface of the polymer-copper mixed layer to form a first copper layer, and the beam current intensity of the low-energy copper ion beam is <10mA; using electron beam evaporation, depositing a second copper layer on the surface of the first copper layer; depositing a low-energy tin ion beam on the surface of the second copper layer to form a tin anti-oxidation layer, and the beam current intensity of the low-energy tin ion beam is <10mA, to obtain a copper-plated polymer film. The preparation method provided by the present invention can prepare a copper-plated polymer film with a thin copper layer thickness and high bonding strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thin film surface metallization, and in particular to a preparation method of a copper-plated polymer film and a device for using the same. Background Art

[0002] COF (Chip On Film) refers to chip bonding packaging on thin films, which is widely used in the field of display devices. With the rapid development of the electronics and communications industries, the demand for displays is increasing day by day, and the development trend of related products is light, thin and flexible, which requires a new generation of packaging products with high density, small size and easy bending to meet the above needs. It is in this context that COF technology has rapidly developed and grown, becoming a major packaging form for driver ICs of flat-panel displays such as LCDs and PDPs, and then an important component of these display modules. COF technology has become one of the mainstream trends in driver IC packaging for future flat-panel displays.

[0003] Currently, the most commonly used COF is mainly prepared through the TAPE process. First, copper is plated on the polymer surface by magnetron sputtering to obtain a copper-plated polymer film. Then, the copper-plated polymer film is exposed and etched by LCD / TFT to pattern the metal layer to form a metal wiring layer.

[0004] In order to prepare COF with finer circuit patterns, the thickness of the sputtered copper plating layer on the surface of the copper-plated polymer film is generally required to be less than 20μm, or even thinner than 9μm, 5μm or even 3μm ultra-thin copper plating layer, so as to shorten the etching time as much as possible, reduce side etching, and obtain fine circuits.

[0005] However, the existing method of copper plating on the polymer surface by magnetron sputtering has a low bonding strength between the copper-plated polymer film substrate and the copper metal, which may cause the copper plating layer to fall off directly, especially under high temperature environment; and the thinner the copper plating layer, the weaker the bonding strength between the two. Summary of the invention

[0006] In view of this, the present invention provides a method for preparing a copper-plated polymer film and a device for using the same. The method for preparing a copper-plated polymer film provided by the present invention can prepare a copper-plated polymer film with a thin copper layer thickness and high bonding strength.

[0007] The present invention provides a method for preparing a copper-plated polymer film, comprising the following steps:

[0008] (1) injecting a high-energy copper ion beam into the surface of the polymer film to form a polymer-copper mixed layer on the surface of the polymer film, wherein the beam intensity of the high-energy copper ion beam is ≥10 mA;

[0009] (2) depositing a low-energy copper ion beam on the surface of the polymer-copper mixed layer to form a first copper layer, wherein the beam current intensity of the low-energy copper ion beam is less than 10 mA;

[0010] (3) depositing a second copper layer on the surface of the first copper layer by electron beam evaporation;

[0011] (4) Depositing a low-energy tin ion beam on the surface of the second copper layer to form a tin anti-oxidation layer, wherein the beam intensity of the low-energy tin ion beam is less than 10 mA, thereby obtaining a copper-plated polymer film.

[0012] Preferably, in step (1), the beam current intensity of the high-energy copper ion beam is 10 to 100 mA, and the energy of the high-energy copper ion beam is 10 to 40 keV.

[0013] Preferably, in step (2), the beam current intensity of the low-energy copper ion beam is 2-10 mA, and the energy of the low-energy copper ion beam is 500 eV-10 keV.

[0014] Preferably, in step (3), the power of the electron beam evaporation is 3 to 10 kW; in step (4), the beam current intensity of the low-energy tin ion beam is 2 to 10 mA, and the arc starting frequency is 10 to 50 Hz.

[0015] Preferably, the thickness of the polymer-copper mixed layer and the first copper layer are independently 1-30 nm; the thickness of the second copper layer is 1-5 μm; and the thickness of the tin anti-oxidation layer is 1-20 nm.

[0016] Preferably, during the process from step (1) to step (4), the polymer film moves at a uniform speed, and the moving speed of the polymer film is independently 0.5 to 1 m / min.

[0017] Preferably, before injecting the high-energy copper ion beam into the surface of the polymer film, the method further includes: etching the polymer film with a mixed gas ion beam; the mixed gas ion beam is a mixed gas ion beam of hydrogen ions and argon ions, and the volume percentage of hydrogen ions in the mixed gas ion beam is 0.05-0.2%.

[0018] Preferably, the beam intensity of the mixed gas ion beam is 0.5-5A.

[0019] The present invention provides a device used in the preparation method described in the above technical solution, comprising:

[0020] A first vacuum chamber 5 - 1 , wherein a high-energy copper ion source and a cold roller are disposed in the first vacuum chamber 5 - 1 ;

[0021] a second vacuum chamber 5-2 whose polymer inlet is connected to the polymer outlet of the first vacuum chamber 5-1, wherein the second vacuum chamber 5-2 is provided with a first chamber and a second chamber, wherein the first chamber is provided with a low-energy copper ion source and a cold roller, and the second chamber is provided with a copper target and a cold roller, wherein the polymer inlet of the first chamber is connected to the polymer outlet of the first vacuum chamber 5-1, and the polymer inlet of the second chamber is connected to the polymer outlet of the first chamber;

[0022] A third vacuum chamber 5 - 3 whose polymer inlet is connected to the polymer outlet of the second vacuum chamber 5 - 2 , wherein a low-energy tin ion source and a cold roller are arranged in the third vacuum chamber 5 - 3 .

[0023] Preferably, it further comprises a fourth vacuum chamber 5 - 4 whose polymer outlet is connected to the polymer inlet of the first vacuum chamber 5 - 1 , and a high-energy gas ion source and a cold roller are arranged in the fourth vacuum chamber 5 - 4 .

[0024] The present invention provides a method for preparing a copper-plated polymer film, comprising the following steps: (1) injecting a high-energy copper ion beam into the surface of a polymer film to form a polymer-copper mixed layer on the surface of the polymer film, wherein the beam current intensity of the high-energy copper ion beam is ≥10 mA; (2) depositing a low-energy copper ion beam on the surface of the polymer-copper mixed layer to form a first copper layer, wherein the beam current intensity of the low-energy copper ion beam is less than 10 mA; (3) using electron beam evaporation to deposit a second copper layer on the surface of the first copper layer; and (4) depositing a low-energy tin ion beam on the surface of the second copper layer to form a tin anti-oxidation layer, wherein the beam current intensity of the low-energy tin ion beam is less than 10 mA, thereby obtaining a copper-plated polymer film. The preparation method provided by the present invention first uses a high-energy copper ion beam with a beam intensity of ≥10mA to inject into the surface of the polymer film, and the high-energy copper ion beam with a beam intensity of ≥10mA is used to modify the surface of the polymer to form a built-in polymer-copper mixed layer, and then a low-energy copper ion beam with a beam intensity of <10mA is deposited on the surface of the polymer-copper mixed layer. The formed copper layer and the polymer-copper mixed layer have high energy and high bonding strength, which significantly improves the bonding strength between the copper layer and the polymer film; then the second copper layer is deposited by electron beam evaporation to increase the thickness of the copper layer; finally, the present invention uses a low-energy tin ion beam to deposit a tin anti-oxidation layer on the surface of the copper layer, and a tin anti-oxidation layer that uniformly covers the copper layer can be obtained, which effectively reduces the oxidation of the copper layer, thereby preventing oxygen atoms from penetrating between the polymer and the copper layer, and reducing the bonding strength between the two. Therefore, the preparation method of the copper-plated polymer film provided by the present invention can prepare a copper-plated polymer film with a thin copper layer thickness and a high bonding strength. The results of the embodiments show that the copper-plated polymer film prepared by the preparation method provided by the present invention has a bonding strength of >1.1N / mm, and the bonding strength does not decrease after being placed for 90 days. Its bending resistance is tested with a bending angle of >150°, and the number of folding times is >1000 times.

[0025] The present invention provides a device used in the preparation method described in the above technical solution, comprising: a first vacuum chamber 5-1, wherein a high-energy copper ion source and a cold roller are arranged in the first vacuum chamber 5-1; a second vacuum chamber 5-2 whose polymer inlet is connected to the polymer outlet of the first vacuum chamber 5-1, wherein the second vacuum chamber 5-2 is provided with a first chamber and a second chamber, wherein a low-energy copper ion source and a cold roller are arranged in the first chamber, wherein a copper target and a cold roller are arranged in the second chamber, wherein the polymer inlet of the first chamber is connected to the polymer outlet of the first vacuum chamber 5-1, and the polymer inlet of the second chamber is connected to the polymer outlet of the first chamber; and a third vacuum chamber 5-3 whose polymer inlet is connected to the polymer outlet of the second vacuum chamber 5-2, wherein a low-energy tin ion source and a cold roller are arranged in the third vacuum chamber 5-3. The device provided by the present invention adopts a vacuum chamber connection and a cold roller connection mode for one-step molding, is simple to operate, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A diagram of a device provided for an embodiment of the present invention;

[0027] 1-unwinding shaft, 2-1-first cold roller, 2-2-second cold roller, 2-3-third cold roller, 2-4-fourth cold roller, 2-5-fifth cold roller, 2-6-sixth cold roller, 2-7-seventh cold roller, 2-8-eighth cold roller, 2-9-ninth cold roller, 2-10-tenth cold roller, 2-11-eleventh cold roller, 2-12-twelfth cold roller, 3-1-first conveying roller, 3-2-second conveying roller, 3-3-third conveying roller, 3-4-fourth conveying roller, 3-5-fifth conveying roller, 3-6-sixth conveying roller, 3-7-seventh conveying roller, 3-8-eighth conveying roller, 3-9-ninth conveying roller, 3-10-tenth conveying roller, 3-11-eleventh conveying roller, 3-12-twelfth conveying roller, 3-13-thirteenth conveying roller, 3-14-the fourteenth conveying roller, 4-1-the first high-energy gas ion source, 4-2-the second high-energy gas ion source, 4-3-the first high-energy copper ion source, 4-4-the second high-energy copper ion source, 4-5-the third high-energy copper ion source, 4-6-the fourth high-energy copper ion source, 4-7-the first low-energy copper ion source, 4-8-the second low-energy copper ion source, 4-9-the third low-energy copper ion source, 4-10-the first copper target, 4-11-the second copper target, 4-12-the third copper target, 4-13-the first low-energy tin ion source, 4-14-the second low-energy tin ion source, 4-15-the third low-energy tin ion source, 4-16-the fourth low-energy tin ion source, 5-1-the first vacuum chamber, 5-2-the second vacuum chamber, 5-3-the third vacuum chamber, 5-4-the fourth vacuum chamber, 6-polymer film, 7-winding shaft;

[0028] Figure 2A process flow chart provided for the implementation of the present invention;

[0029] Figure 3 The bonding strength test results of the copper-plated polymer films prepared in Examples 1 to 4 and Comparative Examples 1 and 2;

[0030] Figure 4 The bonding strength test results of the copper-plated polymer films prepared in Examples 1 to 4 and Comparative Examples 1 and 2 after being placed for 90 days;

[0031] Figure 5 The bending performance test results of the copper-plated polymer films prepared in Examples 1 to 4 and Comparative Examples 1 and 2 are shown. DETAILED DESCRIPTION

[0032] The present invention provides a method for preparing a copper-plated polymer film, comprising the following steps:

[0033] (1) injecting a high-energy copper ion beam into the surface of the polymer film to form a polymer-copper mixed layer on the surface of the polymer film, wherein the beam intensity of the high-energy copper ion beam is ≥10 mA;

[0034] (2) depositing a low-energy copper ion beam on the surface of the polymer-copper mixed layer to form a first copper layer, wherein the beam current intensity of the low-energy copper ion beam is less than 10 mA;

[0035] (3) depositing a second copper layer on the surface of the first copper layer by electron beam evaporation;

[0036] (4) Depositing a low-energy tin ion beam on the surface of the second copper layer to form a tin anti-oxidation layer, wherein the beam intensity of the low-energy tin ion beam is less than 10 mA, thereby obtaining a copper-plated polymer film.

[0037] The invention injects a high-energy copper ion beam into the surface of a polymer film to form a polymer-copper mixed layer on the surface of the polymer film, and the beam current intensity of the high-energy copper ion beam is ≥10mA.

[0038] In the present invention, the polymer film is preferably a polyimide film, a polytetrafluoroethylene film, a high-speed hydrocarbon film or a polystyrene film.

[0039] In the present invention, the thickness of the polymer film is preferably 10 to 38 μm, more preferably 15 to 30 μm.

[0040] In the present invention, the width of the polymer film is preferably 250 to 500 mm.

[0041] In the present invention, a high-energy copper ion beam is injected into the surface of the polymer film. The present invention preferably also includes: etching the polymer film with a mixed gas ion beam; the mixed gas ion beam is a mixed gas ion beam of hydrogen ions and argon ions, and the volume percentage of hydrogen ions in the mixed gas ion beam is 0.05-0.2%.

[0042] In the present invention, the etching is preferably performed in a vacuum environment.

[0043] In the present invention, the mixed gas ion beam is preferably a mixed gas ion beam of hydrogen ions and argon ions, and the volume percentage of hydrogen ions in the mixed gas ion beam is preferably 0.05-0.2%, more preferably 0.08-0.15%.

[0044] In the present invention, the beam current intensity of the mixed gas ion beam is 0.5-5A, more preferably 0.8-4.5A.

[0045] In the present invention, the mixed gas ion beam is obtained by discharging a mixed gas ion beam source, and the flow rate of the mixed gas ion beam source is preferably 100 to 400 sccm, and more preferably 150 to 380 sccm.

[0046] In the present invention, during the etching, the polymer film moves at a uniform speed, and the moving speed of the polymer film is preferably 0.5 to 1 m / min, and more preferably 0.65 to 0.8 m / min.

[0047] The present invention preferably uses a mixed gas ion beam to etch the polymer film. After etching, the roughness of the polymer film surface is preferably ≤20%, and the hydrophilic angle of the polymer film surface after etching is ≤45°; this is beneficial to further improve the bonding ability between the copper plating layer and the polymer film.

[0048] The present invention preferably uses a mixed gas ion beam of hydrogen ions and argon ions to etch the polymer film, wherein the hydrogen ion beam can react with the polymer to form hydrogen bonds; the argon ion beam can etch the surface of the polymer to increase the roughness of the polymer surface. The present invention preferably sets the volume percentage of hydrogen ions in the mixed gas ions to 0.05-0.2%, which is beneficial to making the roughness of the etched polymer preferably ≤20%, and the hydrophilic angle ≤45°, which is beneficial to further improve the bonding ability between the copper plating layer and the polymer.

[0049] In the present invention, both surfaces of the polymer are preferably etched.

[0050] In the present invention, the beam current intensity of the high-energy copper ion beam is ≥10 mA, preferably 10 to 100 mA, and more preferably 15 to 90 mA.

[0051] In the present invention, the energy of the high-energy copper ion beam is preferably 10 to 40 keV, more preferably 15 to 35 keV.

[0052] In the present invention, the high-energy copper ion beam is preferably obtained by a first discharge of a high-energy copper ion source in a first magnetic field.

[0053] In the present invention, the voltage of the first magnetic field is preferably 5 to 10 kV, more preferably 5.5 to 8 kV. In the present invention, the frequency of the first magnetic field is preferably 1 to 10 Hz, more preferably 4 to 7 Hz.

[0054] The present invention uses a high-energy copper ion beam with a beam intensity of ≥10mA to inject into the surface of the polymer film. The high-energy copper ion beam has high energy and is more conducive to being injected into the interior of the polymer surface when in contact with the polymer film to form a built-in polymer-copper mixed layer.

[0055] At the same time, the present invention uses a high-energy copper ion beam with a beam intensity of ≥10mA to inject into the surface of the polymer film, which can greatly increase the copper ionization rate, thereby increasing the energy of the copper ion beam, which is more conducive to injection into the interior of the polymer film to form a built-in polymer-copper mixed layer.

[0056] In the present invention, when the high-energy copper ion beam is injected, the polymer film preferably moves at a uniform speed, and the moving speed of the polymer is preferably 0.5 to 1 m / min, more preferably 0.65 to 0.8 m / min.

[0057] The present invention uses a high-energy copper ion beam with a beam current intensity of ≥10mA to inject into the surface of the polymer film, so as to obtain a high-energy copper ion beam. The efficiency of injecting the copper ion beam into the polymer film is improved, which is beneficial to increasing the running speed of the polymer film, improving the preparation efficiency of the copper-plated polymer film, and reducing the production cost.

[0058] In the present invention, the thickness of the polymer-copper mixed layer formed after copper injection is preferably 1 to 50 nm, more preferably 5 to 45 nm.

[0059] In the present invention, the high energy copper ion beam implantation is preferably performed in a vacuum environment.

[0060] In the present invention, high energy copper ion beams are preferably implanted into both surfaces of the polymer.

[0061] After obtaining the polymer-copper mixed layer, the present invention deposits a low-energy copper ion beam (hereinafter referred to as the first deposition) on the surface of the polymer-copper mixed layer to form a first copper layer, wherein the beam current intensity of the low-energy copper ion beam is less than 10 mA.

[0062] In the present invention, the beam current intensity of the low-energy copper ion beam is less than 10 mA, preferably 4 to 8 mA.

[0063] In the present invention, the energy of the low-energy copper ion beam is preferably 4 to 8 keV.

[0064] In the present invention, the low-energy copper ion beam is preferably obtained by a second discharge of a low-energy copper ion source in a second magnetic field, and the arc starting current during the second discharge is preferably 50 to 120 A, more preferably 65 to 100 A. In the present invention, the mixing magnetic field strength of the second magnetic field is 1 to 10 KA, more preferably 2.5 to 8 KA. In the present invention, the frequency of the second magnetic field is preferably 1 to 100 Hz, more preferably 5 to 90 Hz.

[0065] In the present invention, during the low-energy copper ion beam deposition, the polymer film preferably moves at a uniform speed, and the moving speed of the polymer is preferably 0.5 to 1 m / min, more preferably 0.65 to 0.8 m / min.

[0066] The present invention uses a low-energy copper ion beam with a beam intensity of less than 10mA to deposit on the surface of the polymer film. The low-energy copper ion beam can migrate on the surface of the polymer-copper mixed layer, effectively improving the coverage and density of the first copper layer on the polymer surface and reducing pinhole formation.

[0067] Moreover, the present invention uses a low-energy copper ion beam with a beam intensity of less than 10mA to be deposited on the surface of the polymer film. The low-energy copper ion beam can achieve covalent bond connection with the polymer-copper mixed layer. Compared with physical adsorption, the preparation method provided by the present invention has a stronger bonding ability between the first copper-plated layer and the polymer film.

[0068] In the present invention, the thickness of the first copper layer is preferably 1 to 50 nm, more preferably 5 to 45 nm.

[0069] In the present invention, the first deposition is preferably performed in a vacuum environment.

[0070] In the present invention, it is preferred that the first deposition is performed on both surfaces of the polymer.

[0071] After forming the first copper layer, the present invention uses electron beam evaporation to deposit (hereinafter referred to as second deposition) a second copper layer on the surface of the first copper layer.

[0072] In the present invention, the power of the electron beam evaporation is preferably 3 to 10 kW, more preferably 4 to 8 kW.

[0073] In the present invention, the thickness of the second copper layer is preferably 1 to 5 μm, more preferably 1.5 to 3 μm.

[0074] In the present invention, when the second copper layer is deposited by electron beam evaporation, the polymer film preferably moves at a uniform speed, and the moving speed of the polymer is preferably 0.5 to 1 m / min, more preferably 0.65 to 0.8 m / min.

[0075] After forming the second copper layer, the present invention deposits a low-energy tin ion beam (hereinafter referred to as the third deposition) on the surface of the copper layer to form a tin anti-oxidation layer, wherein the beam current intensity of the low-energy tin ion beam is less than 10 mA, to obtain a copper-plated polymer film.

[0076] In the present invention, the beam current intensity of the low-energy tin ion beam is less than 10 mA, preferably 4 to 8 mA.

[0077] In the present invention, the energy of the low-energy tin ion beam is preferably 4-8 keV.

[0078] In the present invention, since the melting point of tin is 231°C, it is very easy for the local temperature to be too high and melt to occur during the third deposition process; during the Sn arc deposition process, the arc starting method of the present invention is preferably pulse arc starting, and the arc starting frequency is preferably 10 to 50 Hz; at the same time, the tin target cooling structure can fully cool the tin target to ensure that it can start the arc normally. The temperature of the cooling water in the target is preferably -10 to -30°C.

[0079] In the present invention, when the low-energy tin ion beam deposits the tin anti-oxidation layer, the polymer film preferably moves at a uniform speed, and the moving speed of the polymer is preferably 0.5 to 1 m / min, more preferably 0.65 to 0.8 m / min.

[0080] The present invention can effectively prevent the copper layer from being oxidized by depositing a tin layer on the surface of the copper layer, and oxygen atoms diffuse to the interface between the polymer and the copper layer, thereby reducing the bonding strength between the copper layer and the polymer.

[0081] The present invention uses a low-energy tin ion beam with a beam current intensity of less than 10 mA to be deposited on the surface of the copper layer, thereby obtaining a dense and uniform tin anti-oxidation layer.

[0082] In the present invention, the thickness of the tin anti-oxidation layer is preferably 1 to 20 nm, more preferably 2 to 15 nm.

[0083] In the present invention, the deposition of tin is preferably performed in a vacuum environment.

[0084] In the present invention, tin is preferably deposited on both surfaces of the polymer.

[0085] The present invention provides a device used in the preparation method described in the above technical solution, comprising:

[0086] A first vacuum chamber 5 - 1 , wherein a high-energy copper ion source and a cold roller are disposed in the first vacuum chamber 5 - 1 ;

[0087] a second vacuum chamber 5-2 whose polymer inlet is connected to the polymer outlet of the first vacuum chamber 5-1, wherein the second vacuum chamber 5-2 is provided with a first chamber and a second chamber, wherein the first chamber is provided with a low-energy copper ion source and a cold roller, and the second chamber is provided with a copper target and a cold roller, wherein the polymer inlet of the first chamber is connected to the polymer outlet of the first vacuum chamber (5-1), and the polymer inlet of the second chamber is connected to the polymer outlet of the first chamber;

[0088] A third vacuum chamber 5 - 3 whose polymer inlet is connected to the polymer outlet of the second vacuum chamber 5 - 2 , wherein a low-energy tin ion source and a cold roller are arranged in the third vacuum chamber 5 - 3 .

[0089] The device provided by the present invention preferably further comprises a fourth vacuum chamber 5-4 whose polymer outlet is connected to the polymer inlet of the first vacuum chamber 5-1, and the fourth vacuum chamber 5-4 is preferably provided with a high-energy gas ion source and a cold roller.

[0090] As a specific embodiment of the present invention, the fourth vacuum chamber 5-4 is provided with an unwinding shaft 1, and the unwinding shaft 1 is used to output the polymer film 6. The unwinding shaft 1 is arranged on the inner bottom surface of the fourth vacuum chamber 5-4.

[0091] As a specific embodiment of the present invention, the fourth vacuum chamber 5-4 is provided with a first cold roller 2-1, and the first cold roller 2-1 is used to convey the polymer film 6 output from the unwinding shaft 1. The first cold roller 2-1 and the unwinding shaft 1 are at the same level.

[0092] As a specific embodiment of the present invention, the fourth vacuum chamber 5-4 is provided with a first high-energy gas ion source 4-1, and the first high-energy gas ion source 4-1 is used to etch the side of the polymer film 6 on the first cold roller 2-1 that is not in contact with the surface of the first cold roller 2-1. In the present invention, the first high-energy gas ion source 4-1 and the first cold roller 2-1 are located on the same horizontal plane.

[0093] As a specific embodiment of the present invention, the fourth vacuum chamber 5-4 is provided with a first conveying roller 3-1 and a second conveying roller 3-2, and the first conveying roller 3-1 and the second conveying roller 3-2 are used to convey the polymer film 6 from the first cold roller 2-1 to the second cold roller 2-2, and at the same time, the surface of the polymer film 6 in contact with the first cold roller 2-1 and the surface of the polymer film 6 in contact with the second cold roller 2-2 are different, so that the surface of the polymer film 6 etched on the first cold roller 2-1 can be different from the surface etched on the second cold roller 2-2, so that both sides of the polymer film 6 can be etched at the same time. In the present invention, the first conveying roller 3-1 and the second conveying roller 3-2 are located on the same horizontal plane, and the vertical height of the first conveying roller 3-1 and the second conveying roller 3-2 is greater than the vertical height of the first cold roller 2-1, and less than the vertical height of the second cold roller 2-2.

[0094] As a specific embodiment of the present invention, the fourth vacuum chamber 5-4 is provided with a second cold roller 2-2. In the present invention, the second cold roller 2-2 is used to convey the polymer film 6 output by the first cold roller 2-1. The vertical height of the second cold roller 2-2 is greater than the vertical heights of the first conveying roller 3-1 and the second conveying roller 3-2.

[0095] As a specific embodiment of the present invention, the fourth vacuum chamber 5-4 is provided with a second high-energy gas ion source 4-2, and the second high-energy gas ion source 4-2 is used to etch the side of the polymer film 6 on the second cold roller 2-2 that is not in contact with the surface of the second cold roller 2-2. In the present invention, the second high-energy gas ion source 4-2 is preferably located on the same horizontal plane as the second cold roller 2-2.

[0096] The device provided by the present invention comprises a first vacuum chamber 5 - 1 , in which a high-energy copper ion source and a cold roller are arranged.

[0097] As a specific embodiment of the present invention, the first vacuum chamber 5 - 1 is provided with a third cold roller 2 - 3 , and the third cold roller 2 - 3 is used to convey the polymer film 6 output by the second cold roller 2 - 2 .

[0098] As a specific embodiment of the present invention, the first vacuum chamber 5-1 is provided with a first high-energy copper ion source 4-3, and the first high-energy copper ion source 4-3 is used to inject copper into the side of the polymer film 6 on the third cold roller 2-3 that is not in contact with the surface of the third cold roller 2-3. In the present invention, the first high-energy copper ion source 4-3 is preferably located on the same horizontal plane as the third cold roller 2-3.

[0099] As a specific embodiment of the present invention, the first vacuum chamber 5-1 is provided with a third conveying roller 3-3 and a fourth conveying roller 3-4, and the third conveying roller 3-3 and the fourth conveying roller 3-4 are used to convey the polymer film 6 from the third cold roller 2-3 to the fourth cold roller 2-4, and at the same time, the surface of the polymer film 6 in contact with the third cold roller 2-3 and the surface of the polymer film 6 in contact with the fourth cold roller 2-4 are different, so that the surface of the polymer film 6 injected with copper on the third cold roller 2-3 and the surface injected with copper on the fourth cold roller 2-4 can be different, so that copper can be injected on both sides of the polymer film 6 at the same time. The third conveying roller 3-3 and the fourth conveying roller 3-4 are located on the same horizontal plane as the third cold roller 2-3.

[0100] As a specific embodiment of the present invention, the first vacuum chamber 5-1 is provided with a fourth cold roller 2-4, and the fourth cold roller 2-4 is used to convey the polymer film 6 output by the third cold roller 2-3. In the present invention, the fourth cold roller 2-4 is preferably located on the same horizontal plane as the third cold roller 2-3.

[0101] As a specific embodiment of the present invention, the first vacuum chamber 5-4 is provided with a second high-energy copper ion source 4-4, and the second high-energy copper ion source 4-4 is used to inject copper into the side of the polymer film 6 on the fourth cold roller 2-4 that is not in contact with the surface of the fourth cold roller 2-4. In the present invention, the second high-energy copper ion source 4-4 is preferably located on the same horizontal plane as the fourth cold roller 2-4.

[0102] As a specific embodiment of the present invention, the first vacuum chamber 5-1 is provided with a fifth cold roller 2-5, which is used to convey the polymer film 6 output by the fourth cold roller 2-4. The vertical height of the fifth cold roller 2-5 is greater than the vertical height of the fourth cold roller 2-4.

[0103] As a specific embodiment of the present invention, the first vacuum chamber 5-1 is provided with a third high-energy copper ion source 4-5, and the third high-energy copper ion source 4-5 is used to inject copper into the side of the polymer film 6 located on the fifth cold roller 2-5 that is not in contact with the surface of the fifth cold roller 2-5. In the present invention, the third high-energy copper ion source 4-5 is preferably located on the same horizontal plane as the fifth cold roller 2-5.

[0104] As a specific embodiment of the present invention, the first vacuum chamber 5-1 is provided with a fourth high-energy copper ion source 4-6, and the fourth high-energy copper ion source 4-6 is used to inject copper into the side of the polymer film 6 located on the fifth cold roller 2-5 that is not in contact with the surface of the fifth cold roller 2-5. In the present invention, the fourth high-energy copper ion source 4-6 is preferably located on the same horizontal plane as the fifth cold roller 2-5.

[0105] As a specific embodiment of the present invention, the first vacuum chamber 5-1 is provided with a fifth conveying roller 3-5, and the fifth conveying roller 3-5 is used to output the polymer film 6 from the first vacuum chamber 5-1. The fifth conveying roller 3-5 and the fifth cold roller 2-5 are located at the same level.

[0106] The device provided by the present invention includes a second vacuum chamber 5-2 whose polymer inlet is connected to the polymer outlet of the first vacuum chamber 5-1, and a first chamber and a second chamber are arranged in the second vacuum chamber 5-2, a low-energy copper ion source and a cold roller are arranged in the first chamber, a copper target and a cold roller are arranged in the second chamber, the polymer inlet of the first chamber is connected to the polymer outlet of the first vacuum chamber (5-1), and the polymer inlet of the second chamber is connected to the polymer outlet of the first chamber.

[0107] As a specific embodiment of the present invention, the first chamber of the second vacuum chamber 5-2 is provided with a sixth conveying roller 3-6, and the sixth conveying roller 3-6 is used to input the polymer film 6 into the first chamber of the second vacuum chamber 5-2. The sixth conveying roller 3-6 is located at the same level as the fifth conveying roller 3-5.

[0108] As a specific embodiment of the present invention, the first chamber of the second vacuum chamber 5-2 is provided with a sixth cold roller 2-6, which is used to convey the polymer film 6 output by the fifth cold roller 2-5. The sixth cold roller 2-6 and the fifth cold roller 2-5 are located on the same horizontal plane.

[0109] As a specific embodiment of the present invention, the first chamber of the second vacuum chamber 5-2 is provided with a first low-energy copper ion source 4-7, and the first low-energy copper ion source 4-7 is used to deposit copper on the side of the polymer film 6 located on the sixth cold roller 2-6 that is not in contact with the surface of the sixth cold roller 2-6. In the present invention, the first low-energy copper ion source 4-7 is preferably located on the same horizontal plane as the sixth cold roller 2-6.

[0110] As a specific embodiment of the present invention, the first chamber of the second vacuum chamber 5-2 is provided with a second low-energy copper ion source 4-8, and the second low-energy copper ion source 4-8 is used to deposit copper on the side of the polymer film 6 on the sixth cold roller 2-6 that is not in contact with the surface of the sixth cold roller 2-6. In the present invention, the second low-energy copper ion source 4-8 is preferably located on the same horizontal plane as the sixth cold roller 2-6, and is located on both horizontal sides of the sixth cold roller 2-6 with the seventh high-energy copper ion source 4-7.

[0111] As a specific embodiment of the present invention, the first chamber of the second vacuum chamber 5-2 is provided with a seventh conveying roller 3-7, and the seventh conveying roller 3-7 is used to input the polymer film 6 from the sixth cold roller 2-6 to the seventh cold roller 2-7. The vertical height of the seventh conveying roller 3-7 is preferably less than the vertical height of the sixth roller 2-6, and greater than the vertical height of the seventh cold roller 2-7.

[0112] As a specific embodiment of the present invention, the first chamber of the second vacuum chamber 5-2 is provided with a seventh cold roller 2-7, which is used to convey the polymer film 6 output by the sixth cold roller 2-6. The vertical height of the seventh cold roller 2-7 is preferably less than the vertical height of the sixth roller 2-6.

[0113] As a specific embodiment of the present invention, the first chamber of the second vacuum chamber 5-2 is provided with a third low-energy copper ion source 4-9, and the third low-energy copper ion source 4-9 is used to deposit copper on the side of the polymer film 6 on the seventh cold roller 2-7 that is not in contact with the surface of the seventh cold roller 2-7. In the present invention, the third low-energy copper ion source 4-9 is preferably located on the same horizontal plane as the seventh cold roller 2-7.

[0114] As a specific embodiment of the present invention, the first chamber of the second vacuum chamber 5-2 is provided with an eighth conveying roller 3-8 and a ninth conveying roller 3-9, and the eighth conveying roller 3-8 and the ninth conveying roller 3-9 are preferably located on the same horizontal plane, and the vertical heights of the eighth conveying roller 3-8 and the ninth conveying roller 3-9 are preferably less than the vertical height of the seventh cold roller. The eighth conveying roller 3-8 and the ninth conveying roller 3-9 are used to convey the polymer film 6 from the seventh cold roller 2-7 to the eighth cold roller 2-8, and at the same time, the surface of the polymer film 6 in contact with the seventh cold roller 2-7 and the surface of the polymer film 6 in contact with the eighth cold roller 2-8 are different, so that the surface of the polymer film 6 on which copper is deposited on the seventh cold roller 2-7 is different from the surface on which copper is deposited on the eighth cold roller 2-8, so that copper is deposited on both sides of the polymer film 6 at the same time.

[0115] As a specific embodiment of the present invention, the second chamber of the second vacuum chamber 5-2 is provided with an eighth cold roller 2-8, and the eighth cold roller 2-8 is used to convey the polymer film 6 output by the seventh cold roller 2-7. The vertical height of the eighth cold roller 2-8 is preferably less than the vertical heights of the eighth conveying roller 3-8 and the ninth conveying roller 3-9.

[0116] As a specific embodiment of the present invention, the second chamber of the second vacuum chamber 5-2 is provided with a first copper target 4-10, and the first copper target 4-10 is used to deposit copper on the side of the polymer film 6 on the eighth cold roller 2-8 that is not in contact with the surface of the eighth cold roller 2-8. In the present invention, the first copper target 4-10 is preferably located on the same horizontal plane as the eighth cold roller 2-8.

[0117] As a specific embodiment of the present invention, the second chamber of the second vacuum chamber 5-2 is provided with a ninth cold roller 2-9, and the ninth cold roller 2-9 is used to convey the polymer film 6 output by the eighth cold roller 2-8. The vertical height of the ninth cold roller 2-9 is preferably less than the vertical height of the eighth cold roller 2-8, and the ninth cold roller 2-9 and the eighth cold roller 2-8 are located on the same vertical plane.

[0118] As a specific embodiment of the present invention, the second chamber of the second vacuum chamber 5-2 is provided with a second copper target 4-11, and the second copper target 4-11 is used to deposit copper on the side of the polymer film 6 on the ninth cold roller 2-9 that is not in contact with the surface of the ninth cold roller 2-9. In the present invention, the second copper target 4-11 is preferably located on the same horizontal plane as the ninth cold roller 2-9.

[0119] As a specific embodiment of the present invention, the second chamber of the second vacuum chamber 5-2 is provided with a third copper target 4-12, and the third copper target 4-12 is used to deposit copper on the side of the polymer film 6 on the ninth cold roller 2-9 that is not in contact with the surface of the ninth cold roller 2-9. In the present invention, the third copper target 4-12 is preferably located on the same horizontal plane as the ninth cold roller 2-9. The second copper target 4-11 and the third copper target 4-12 are respectively located on both sides of the ninth cold roller 2-9.

[0120] As a specific embodiment of the present invention, the second chamber of the second vacuum chamber 5-2 is provided with a tenth conveying roller 3-10, and the tenth conveying roller 3-10 is used to output the polymer film 6 from the second vacuum chamber 5-2. The tenth conveying roller 3-10 is preferably located on the same horizontal plane as the eighth cold roller.

[0121] The device provided by the present invention comprises a third vacuum chamber 5-3 whose polymer inlet is connected to the polymer outlet of the second vacuum chamber 5-2, and a low-energy tin ion source and a cold roller are arranged in the third vacuum chamber 5-3.

[0122] As a specific embodiment of the present invention, the third vacuum chamber 5-3 is provided with an eleventh conveying roller 3-11, and the eleventh conveying roller 3-11 is used to input the polymer film 6 into the third vacuum chamber 5-3. The eleventh conveying roller 3-11 is preferably located on the same horizontal plane as the tenth conveying roller 3-10.

[0123] As a specific embodiment of the present invention, the third vacuum chamber 5-3 is provided with a tenth cold roller 2-10, and the tenth cold roller 2-10 is used to convey the polymer film 6 output by the ninth cold roller 2-9. The tenth cold roller 2-10 is preferably located on the same horizontal plane as the ninth cold roller 2-9.

[0124] As a specific embodiment of the present invention, the third vacuum chamber 5-3 is provided with a first low-energy tin ion source 4-13, and the first low-energy tin ion source 4-13 is used to deposit tin on the side of the polymer film 6 located on the tenth cold roller 2-10 that is not in contact with the surface of the tenth cold roller 2-10. In the present invention, the first low-energy tin ion source 4-13 is preferably located on the same horizontal plane as the tenth cold roller 2-10.

[0125] As a specific embodiment of the present invention, the third vacuum chamber 5-3 is provided with a second low-energy tin ion source 4-14, and the second low-energy tin ion source 4-14 is used to deposit tin on the side of the polymer film 6 located on the tenth cold roller 2-10 that is not in contact with the surface of the tenth cold roller 2-10. In the present invention, the second low-energy tin ion source 4-14 is preferably located on the same horizontal plane as the tenth cold roller 2-10. The thirteenth high-energy copper ion source 4-13 and the second low-energy tin ion source 4-14 are respectively located on both horizontal sides of the tenth cold roller 2-10.

[0126] As a specific embodiment of the present invention, the third vacuum chamber 5-3 is provided with a twelfth conveying roller 3-12, and the twelfth conveying roller 3-11 is used to convey the polymer film 6 from the tenth cold roller 2-10 to the eleventh cold roller 2-11. The vertical height of the twelfth conveying roller 3-12 is preferably greater than the vertical height of the eleventh conveying roller 3-11.

[0127] As a specific embodiment of the present invention, the third vacuum chamber 5-3 is provided with an eleventh cold roller 2-10, and the eleventh cold roller 2-11 is used to convey the polymer film 6 output by the tenth cold roller 2-10. The vertical height of the eleventh cold roller 2-11 is preferably greater than the vertical height of the twelfth conveying roller 3-12.

[0128] As a specific embodiment of the present invention, the third vacuum chamber 5-3 is provided with a thirteenth conveying roller 3-13 and a fourteenth conveying roller 3-14, and the thirteenth conveying roller 3-13 and the fourteenth conveying roller 3-14 are used to convey the polymer film 6 from the eleventh cold roller 2-11 to the twelfth cold roller 2-12, and at the same time realize that the surface of the polymer film 6 in contact with the eleventh cold roller 2-11 and the surface of the polymer film 6 in contact with the twelfth cold roller 2-12 are different, so that the surface of the polymer film 6 on which tin is deposited on the eleventh cold roller 2-11 is different from the surface on which tin is deposited on the twelfth cold roller 2-12, and tin is deposited on both sides of the polymer film 6 at the same time. The thirteenth conveying roller 3-13 and the fourteenth conveying roller 3-14 are preferably located at the same level, and the vertical heights of the thirteenth conveying roller 3-13 and the fourteenth conveying roller 3-14 are preferably greater than the vertical height of the eleventh cold roller.

[0129] As a specific embodiment of the present invention, the third vacuum chamber 5-3 is provided with a twelfth cold roller 2-12, and the twelfth cold roller 2-12 is used to convey the polymer film 6 output by the eleventh cold roller 2-11. The vertical height of the twelfth cold roller 2-12 is preferably greater than the vertical heights of the thirteenth conveying roller 3-13 and the fourteenth conveying roller 3-14.

[0130] As a specific embodiment of the present invention, the third vacuum chamber 5-3 is provided with a third low-energy tin ion source 4-15, and the third low-energy tin ion source 4-15 is used to deposit tin on the side of the polymer film 6 located on the twelfth cold roller 2-12 that is not in contact with the surface of the twelfth cold roller 2-12. In the present invention, the third low-energy tin ion source 4-15 is preferably located on the same horizontal plane as the twelfth cold roller 2-12.

[0131] As a specific embodiment of the present invention, the third vacuum chamber 5-3 is provided with a fourth low-energy tin ion source 4-16, and the fourth low-energy tin ion source 4-16 is used to deposit tin on the side of the polymer film 6 on the twelfth cold roller 2-12 that is not in contact with the surface of the twelfth cold roller 2-12. In the present invention, the fourth low-energy tin ion source 4-16 is preferably located on the same horizontal plane as the twelfth cold roller 2-12. The fifteenth high-energy copper ion source 4-15 and the fourth low-energy tin ion source 4-16 are respectively located on both horizontal sides of the twelfth cold roller 2-12.

[0132] As a specific embodiment of the present invention, the third vacuum chamber 5-3 is provided with a reel 7, and the reel 7 is used to collect the copper-plated polymer film. The reel 7 is preferably located on the same horizontal plane as the eleventh cold roller 2-11.

[0133] As a specific embodiment of the present invention, the diameters of the 2-1-first cold roller, 2-2-second cold roller, 2-3-third cold roller, 2-4-fourth cold roller, 2-5-fifth cold roller, 2-6-sixth cold roller, 2-7-seventh cold roller, 2-8-eighth cold roller, 2-9-ninth cold roller, 2-10-tenth cold roller, 2-11-eleventh cold roller and 2-12-twelfth cold roller are independently 800-1200mm; permanent magnets are arranged inside the first to twelfth cold rollers, and the shielding of ions is achieved by the electromagnetic field to ensure that the first to twelfth cold rollers are not contaminated by ions.

[0134] In the present invention, the system tension of the above device is preferably 0.1-20N, more preferably 0.5-15N.

[0135] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0136] Example 1

[0137] use Figure 1 The device is used to prepare a copper-plated polymer film:

[0138] In the fourth vacuum mode, the unwinding shaft unwinds and uses a mixed gas ion source with a flow rate of 400 sccm. The two surfaces of the polymer film are etched with a mixed gas ion beam. During etching, the volume percentage of hydrogen ions in the mixed gas ion beam is 0.1%, the beam current intensity of the mixed ion beam is 3A, and the travel speed of the polymer film is 0.7 m / min.

[0139] After etching, the polymer film enters the first vacuum chamber, and the high-energy copper ion beam source discharges in the magnetic field to inject the high-energy copper ion beam into the surface of the polymer film. The beam current intensity of the high-energy copper ion beam is 50mA, the energy is 10KeV, and the polymer travel speed is 0.7m / min, forming a 5nm polymer-copper mixed layer.

[0140] After a polymer-copper mixed layer is formed on the polymer surface, the polymer film enters the first chamber of the second vacuum chamber, and a low-energy copper ion beam source is discharged in a magnetic field to deposit a low-energy copper ion beam on the surface of the polymer film to form a first copper layer. The magnetic field intensity is 5kA, the magnetic field frequency is 60Hz, and the discharge arc current is 60A; the low-energy copper ion beam current intensity is 8mA, the energy is 2KeV, and the polymer travel speed is 0.7m / min, forming a 10nm first copper layer;

[0141] Entering the second chamber of the second vacuum chamber, the electron beam evaporation power is 3kW, the polymer travel speed is 0.7m / min, and the second copper layer is deposited with a copper thickness of 2μm;

[0142] After forming the second copper layer, the polymer film enters the third vacuum chamber. The low-energy tin ion beam has a beam current intensity of 8 mA, an energy of 2 KeV, an arcing frequency of 30 Hz, and a polymer travel speed of 0.7 m / min. After forming a 5 nm tin anti-oxidation layer, it is rolled up in the third vacuum chamber.

[0143] Example 2

[0144] use Figure 1 The device is used to prepare a copper-plated polymer film:

[0145] In the fourth vacuum mode, the unwinding shaft unwinds and uses a mixed gas ion source with a flow rate of 400 sccm. The two surfaces of the polymer film are etched with a mixed gas ion beam. During etching, the volume percentage of hydrogen ions in the mixed gas ion beam is 0.1%, the beam current intensity of the mixed ion beam is 3A, and the travel speed of the polymer film is 0.7 m / min.

[0146] After etching, the polymer film enters the first vacuum chamber, and the high-energy copper ion beam source discharges in the magnetic field to inject the high-energy copper ion beam into the surface of the polymer film. The beam current intensity of the high-energy copper ion beam is 50mA, the energy is 80KeV, and the polymer travel speed is 0.7m / min, forming an 8nm polymer-copper mixed layer.

[0147] After a polymer-copper mixed layer is formed on the polymer surface, the polymer film enters the first chamber of the second vacuum chamber, and a low-energy copper ion beam source is discharged in a magnetic field to deposit a low-energy copper ion beam on the surface of the polymer film to form a first copper layer. The magnetic field intensity is 5kA, the magnetic field frequency is 60Hz, and the discharge arc current is 90A; the low-energy copper ion beam current intensity is 8mA, the energy is 2KeV, and the polymer travel speed is 0.7m / min, forming a 20nm first copper layer;

[0148] Entering the second chamber of the second vacuum chamber, the electron beam evaporation power is 5 kW, the polymer travel speed is 0.7 m / min, and the second copper layer is deposited with a copper thickness of 3 μm;

[0149] After forming the second copper layer, the polymer film enters the third vacuum chamber. The low-energy tin ion beam has a beam current intensity of 8 mA, an energy of 2 KeV, an arcing frequency of 30 Hz, and a polymer travel speed of 0.7 m / min. After forming a 5 nm tin anti-oxidation layer, it is rolled up in the third vacuum chamber.

[0150] Example 3

[0151] use Figure 1 The device is used to prepare a copper-plated polymer film:

[0152] In the fourth vacuum mode, the unwinding shaft unwinds and uses a mixed gas ion source with a flow rate of 400 sccm. The two surfaces of the polymer film are etched with a mixed gas ion beam. During etching, the volume percentage of hydrogen ions in the mixed gas ion beam is 0.1%, the beam current intensity of the mixed ion beam is 3A, and the travel speed of the polymer film is 0.7 m / min.

[0153] After etching, the polymer film enters the first vacuum chamber, and the high-energy copper ion beam source discharges in the magnetic field to inject the high-energy copper ion beam into the surface of the polymer film. The beam current intensity of the high-energy copper ion beam is 50mA, the energy is 80KeV, and the polymer travel speed is 0.7m / min, forming an 8nm polymer-copper mixed layer.

[0154] After a polymer-copper mixed layer is formed on the polymer surface, the polymer film enters the first chamber of the second vacuum chamber, and a low-energy copper ion beam source is discharged in a magnetic field to deposit a low-energy copper ion beam on the surface of the polymer film to form a first copper layer. The magnetic field intensity is 5kA, the magnetic field frequency is 60Hz, and the discharge arc current is 100A; the beam current intensity of the low-energy copper ion beam is 8mA, the energy is 2KeV, and the polymer travel speed is 0.7m / min, forming a 30nm first copper layer;

[0155] Entering the second chamber of the second vacuum chamber, the electron beam evaporation power is 3kW, the polymer travel speed is 0.7m / min, and the second copper layer is deposited with a copper thickness of 2μm;

[0156] After forming the second copper layer, the polymer film enters the third vacuum chamber. The low-energy tin ion beam has a beam current intensity of 8 mA, an energy of 2 KeV, an arcing frequency of 30 Hz, and a polymer travel speed of 0.7 m / min. After forming a 5 nm tin anti-oxidation layer, it is rolled up in the third vacuum chamber.

[0157] Example 4

[0158] use Figure 1 The device is used to prepare a copper-plated polymer film:

[0159] In the fourth vacuum mode, the unwinding shaft unwinds and uses a mixed gas ion source with a flow rate of 400 sccm. The two surfaces of the polymer film are etched with a mixed gas ion beam. During etching, the volume percentage of hydrogen ions in the mixed gas ion beam is 0.1%, the beam current intensity of the mixed ion beam is 3A, and the travel speed of the polymer film is 0.7 m / min.

[0160] After etching, the polymer film enters the first vacuum chamber, and the high-energy copper ion beam source discharges in the magnetic field to inject the high-energy copper ion beam into the surface of the polymer film. The beam current intensity of the high-energy copper ion beam is 50mA, the energy is 80KeV, and the polymer travel speed is 0.7m / min, forming an 8nm polymer-copper mixed layer.

[0161] After a polymer-copper mixed layer is formed on the polymer surface, the polymer film enters the first chamber of the second vacuum chamber, and a low-energy copper ion beam source is discharged in a magnetic field to deposit a low-energy copper ion beam on the surface of the polymer film to form a first copper layer. The magnetic field intensity is 5kA, the magnetic field frequency is 60Hz, and the discharge arc current is 90A; the low-energy copper ion beam current intensity is 8mA, the energy is 2KeV, and the polymer travel speed is 0.7m / min, forming a 20nm first copper layer;

[0162] Entering the second chamber of the second vacuum chamber, the electron beam evaporation power is 7kW, the polymer travel speed is 0.7m / min, and the second copper layer is deposited with a copper thickness of 4μm;

[0163] After forming the second copper layer, the polymer film enters the third vacuum chamber. The low-energy tin ion beam has a beam current intensity of 8 mA, an energy of 2 KeV, an arcing frequency of 50 Hz, and a polymer travel speed of 0.7 m / min. After forming a 10 nm tin anti-oxidation layer, it is rolled up in the third vacuum chamber.

[0164] Comparative Example 1

[0165] use Figure 1 The device is used to prepare a copper-plated polymer film:

[0166] In the fourth vacuum mode, the unwinding shaft unwinds and uses a mixed gas ion source with a flow rate of 400 sccm. The two surfaces of the polymer film are etched with a mixed gas ion beam. During etching, the volume percentage of hydrogen ions in the mixed gas ion beam is 0.1%, the beam current intensity of the mixed ion beam is 3A, and the travel speed of the polymer film is 0.7 m / min.

[0167] After etching, the polymer film enters the first vacuum chamber, and the high-energy copper ion beam source discharges in the magnetic field to inject the high-energy copper ion beam into the surface of the polymer film. The beam current intensity of the high-energy copper ion beam is 50mA, the energy is 80KeV, and the polymer travel speed is 0.7m / min, forming an 8nm polymer-copper mixed layer.

[0168] After a polymer-copper mixed layer is formed on the polymer surface, the polymer film enters the first chamber of the second vacuum chamber and directly enters the second chamber from the first chamber;

[0169] After entering the second chamber of the second vacuum chamber, the electron beam evaporation power was 7 kW, the polymer travel speed was 0.7 m / min, and the second copper layer was deposited with a copper thickness of 4 μm;

[0170] After forming the second copper layer, the polymer film enters the third vacuum chamber and is rolled up in the third vacuum chamber.

[0171] Comparative Example 2

[0172] use Figure 1The device is used to prepare a copper-plated polymer film:

[0173] In the fourth vacuum mode, the unwinding shaft unwinds and directly enters the second chamber of the second vacuum chamber. The electron beam evaporation power is 7 kW, the polymer travel speed is 0.7 m / min, and the second copper layer is deposited with a copper thickness of 4 μm.

[0174] After forming the second copper layer, the polymer film enters the third vacuum chamber. The low-energy tin ion beam has a beam current intensity of 8 mA, an energy of 2 KeV, an arcing frequency of 50 Hz, and a polymer travel speed of 0.7 m / min. After forming a 10 nm tin anti-oxidation layer, it is rolled up in the third vacuum chamber.

[0175] Test Case

[0176] The copper-plated polymer films prepared in Examples 1 to 4 and Comparative Examples 1 and 2 were subjected to performance tests. The copper-plated polymer films prepared in Examples 1 to 4 and Comparative Examples 1 and 2 were immediately subjected to bonding tests. The results are as follows: Figure 1 As shown in Table 1, Figure 1 As can be seen from Table 1, except for Comparative Example 2, the bonding strengths of the products prepared in Examples 1 to 4 of the present invention and Comparative Example 1 are all 1.1 N / mm or above, while the bonding strength difference of the film layer directly subjected to electron beam evaporation in Comparative Example 2 is less than 0.6 N / mm.

[0177] After the products prepared in Examples 1 to 4 and Comparative Examples 1 and 2 were placed for 90 days, a bonding test was conducted. The results are as follows: Figure 4 As shown in Table 1, Figure 4 As can be seen from Table 1, the bonding strength of the copper-plated polymer films prepared in Examples 1 to 4 of the present invention is the same as that of the films just deposited with Cu film; while that of Comparative Example 1 is significantly decreased because the copper layer is oxidized and oxygen atoms enter the interface between the copper layer and the polymer, causing the bonding strength to deteriorate.

[0178] The copper-plated polymer films prepared in Examples 1 to 4 and Comparative Examples 1 and 2 were tested for the number of folding resistances. The bending angle during the test was greater than 150°. The test results are as follows: Figure 5 As shown in Table 1, Figure 5 As can be seen from Table 1, except for Comparative Example 2, which has a folding endurance of less than 300 times, the others are all above 1000 times.

[0179] Table 1 Test results of Examples 1 to 4, Comparative Examples 1 and 2

[0180] Serial number Initial bonding strength Bond strength at 90 days Folding times Example 1 1.08 1.07 1192 Example 2 1.21 1.17 1306 Example 3 1.23 1.18 1078 Example 4 1.20 1.21 1132 Comparative Example 1 1.18 0.05 1198 Comparative Example 2 0.56 0.05 296

[0181] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a copper-plated polymer film, characterized in that: The following steps are involved: (1) injecting a high-energy copper ion beam into the surface of the polymer film to form a polymer-copper mixed layer on the surface of the polymer film, wherein the beam intensity of the high-energy copper ion beam is ≥10 mA; (2) depositing a low-energy copper ion beam on the surface of the polymer-copper mixed layer to form a first copper layer, wherein the beam current intensity of the low-energy copper ion beam is less than 10 mA; (3) depositing a second copper layer on the surface of the first copper layer by electron beam evaporation; the thickness of the second copper layer is 1 to 5 μm; (4) depositing a low-energy tin ion beam on the surface of the second copper layer to form a tin anti-oxidation layer, wherein the beam intensity of the low-energy tin ion beam is less than 10 mA, and a copper-plated polymer film is obtained; the thickness of the tin anti-oxidation layer is 1 to 20 nm.

2. The preparation method according to claim 1, characterized in that: In the step (1), the beam current intensity of the high-energy copper ion beam is 10 to 100 mA, and the energy of the high-energy copper ion beam is 10 to 40 keV.

3. The preparation method according to claim 1, characterized in that: In the step (2), the beam current intensity of the low-energy copper ion beam is 2-10 mA, and the energy of the low-energy copper ion beam is 500 eV-10 keV.

4. The preparation method according to claim 1, characterized in that: In the step (3), the power of the electron beam evaporation is 3 to 10 kW; in the step (4), the beam current intensity of the low-energy tin ion beam is 2 to 10 mA, and the arc starting frequency is 10 to 50 Hz.

5. The preparation method according to claim 1, characterized in that: The thickness of the polymer-copper mixed layer and the first copper layer are independently 1 to 30 nm.

6. The preparation method according to claim 1, characterized in that: In the process from step (1) to step (4), the polymer film moves at a uniform speed, and the moving speed of the polymer film is independently 0.5 to 1 m / min.

7. The preparation method according to claim 1, characterized in that: Before injecting the high energy copper ion beam into the polymer film surface, the method also includes: etching the polymer film with a mixed gas ion beam; the mixed gas ion beam is a mixed gas ion beam of hydrogen ions and argon ions, and the volume percentage of hydrogen ions in the mixed gas ion beam is 0.05-0.2%.

8. The preparation method according to claim 7, characterized in that: The beam current intensity of the mixed gas ion beam is 0.5-5A.

9. The device used in the preparation method according to any one of claims 1 to 8, characterized in that: include: A first vacuum chamber (5-1), wherein a high-energy copper ion source and a cold roller are arranged in the first vacuum chamber (5-1); A second vacuum chamber (5-2) whose polymer inlet is connected to the polymer outlet of the first vacuum chamber (5-1), the second vacuum chamber (5-2) is provided with a first chamber and a second chamber, the first chamber is provided with a low-energy copper ion source and a cold roller, the second chamber is provided with a copper target and a cold roller, the polymer inlet of the first chamber is connected to the polymer outlet of the first vacuum chamber (5-1), and the polymer inlet of the second chamber is connected to the polymer outlet of the first chamber; a third vacuum chamber (5-3) whose polymer inlet is connected to the polymer outlet of the second vacuum chamber (5-2), the third vacuum chamber (5-3) is provided with a low-energy tin ion source and a cold roller.

10. The device according to claim 9, characterized in that It also comprises a fourth vacuum chamber (5-4) whose polymer outlet is connected to the polymer inlet of the first vacuum chamber (5-1), and a high-energy gas ion source and a cold roller are arranged in the fourth vacuum chamber (5-4).

Citation Information

Patent Citations

  • Manufacturing method of LCP substrate flexible copper-clad plate and product thereof

    CN108411247A

  • Winding type copper film vacuum coating equipment for circuit board or battery electrode

    CN115710692A